2012
DOI: 10.1075/intp.14.1.05mie
|View full text |Cite
|
Sign up to set email alerts
|

The quotative ‘he/she says’ in interpreted doctor–patient interaction

Abstract: This article examines the different functions of the quotative ‘he/she says’ in an interpreter’s renderings during four medical interviews (Dutch/Russian). First, the quotative is typically used for renderings of doctors’ turns, where it serves to signal a switch in the participation framework and to segment long discourse units by the doctor. Second, in some renderings of the patients’ turns, the quotative also has a disambiguating function, clarifying the status of the interpretation either as a literal one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…As mentioned, one previous study had reported no association between referencing text as a construct and suicidality 30 ; however, we felt that the association of text in quotation marks was worth evaluating as an alternative marker, because of the potential strengths of a case-crossover design, and because of another study's findings that quoted text used in particular clinical circumstances is associated with higher perceived risk. 31 One possible difference between that study and ours is that we used quotation marks to identify quoted phrases, rather than attempting to identify the speaker, or exchanges of views between clinician and patient. Thus, extending the definition of quoted text to the identification of relevant pronouns would be a worthwhile avenue for future research.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As mentioned, one previous study had reported no association between referencing text as a construct and suicidality 30 ; however, we felt that the association of text in quotation marks was worth evaluating as an alternative marker, because of the potential strengths of a case-crossover design, and because of another study's findings that quoted text used in particular clinical circumstances is associated with higher perceived risk. 31 One possible difference between that study and ours is that we used quotation marks to identify quoted phrases, rather than attempting to identify the speaker, or exchanges of views between clinician and patient. Thus, extending the definition of quoted text to the identification of relevant pronouns would be a worthwhile avenue for future research.…”
Section: Discussionmentioning
confidence: 96%
“…However, another investigation found that quoting 'he/she says' increased in records of clinician-patient interactions that involved communication of bad news between doctor and patient. 31 Clinical recording style has received little investigation in the field of suicidology. To our knowledge, research into the use of quotation marks to record verbatim patient statements in notes has not been conducted to date.…”
Section: Introductionmentioning
confidence: 99%
“…In actual practice, studies have shown that interpreters, both professional and novice, often deviate from the direct speech convention (Angermeyer 2009;Bot 2005;Cheung 2012;Dubslaff & Martinsen 2005;Johnen & Meyer 2007;Takimoto & Koshiba 2009;van de Mieroop 2012). It has even been argued that interpreter neutrality suffers less when reported speech is used, since the use of direct speech implies that the interpreter identifies more closely with what is being said (Wallmach 2002).…”
Section: Direct Speech Vs Reported Speechmentioning
confidence: 96%
“…The resulting sense of disassociation may mitigate the effect of the speech on the addressee, who will therefore tend to see the interpreter as non-dominating and less manipulative (Lings 1988, cited in Dubslaff & Martinsen 2005. For example, interpreters may use reported speech when an interpreted utterance is face-threatening (van de Mieroop, 2012): here, the use of reported speech may be perceived as an "implicit stance that avoids alignment with [the] source speaker" (Angermeyer 2009: 5). In addition, the use of reported speech to convey hostile utterances may make the interpreter's rendition more like a description than an accusation or criticism (Komter 2005).…”
Section: Direct Speech Vs Reported Speechmentioning
confidence: 98%
See 1 more Smart Citation